Pengaruh Jenis Kemasan terhadap Mutu Benih Bunga Matahari (Helianthus annuus L.) pada Penyimpanan Tiga Bulan - Salsabilla, Alya; Astiningsih, Anak Agung Made; Mayun, Ida Ayu (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024), 2024)
Effect of Packaging on Quality of Sunflower Seeds ( Helianthus annuus L.) at Three Months Storage. This study aim to determine the effect of packaging on quality of sunflower seeds. This study used a completely randomized design with 6 treatments, namely sealed plastic bag (Kp), gunny sack (Kg), aluminium foil pouch (Ka), glass jar (Tk), plastic jar (Tp) and plastic sack (Kb) with 4 repetitions. The research was conducted at the Plant Breeding and Seed Technology Laboratory, Agronomy and Horticulture Laboratory and Soil Laboratory, Faculty of Agriculture, Udayana University from September 2022-April 2023. The results showed that the storage techniques for 3 months storage had an effect and aluminium foil pouch (Ka) was able to maintain the quality of sunflower seeds well compared to other storage packaging used in this research as indicated by the value of water content (7,38%), 100 seeds weight (6,88 g), electric conductivity (2,29 mmhos/cm), maximum growth potential (92,50%), germination (85%), simultaneous growth (80,83%) and vigor storability (81,67%).